ACUTE TOXICITY OF CADMIUM (Cd) TO VELIGER LARVAE OF FLUTED GIANT CLAM (Tridacna squamosa LAMARCK, 1819) - Werorilangi, Shinta; Afdal, Muh.; Niartiningsih, Andi; Yusuf, Syafyuddin; Massiani, Arniati; Rastina, Rastina (Hasanuddin University, 2018)
Clams have a planktonic period which is sensitive to metal pollutants in the waters. The natural concentration of cadmium (Cd) is relatively low in marine waters but may increase with increasing anthropogenic activity on land that may be lethal to organisms, especially in the sensitive larval stages. The purpose of this study was to analyze the values of 24h-LC50, NOEC (No Observed Effect Concentration), LOEC (Lowest Observed Effect Concentration) and MATC (Maximum Acceptable Toxicant Concentration) along with the impact of acute Cd toxicity on mortality and morphological changes of Tridacna squamosa veliger. The toxicity test used was an acute toxicity test with a static method (4 replications). Acute toxicity tests were performed on veliger phase larvae with short-term exposure (24 hours) on various Cd concentrations ie., 0.1 mg/L, 1 mg/L, 2.5 mg/L, 5 mg/L and 10 mg/L . The 24h-LC50 value was calculated using the Trimmed Spearman-Karber application version 4.1, and the LOEC and NOEC values were analyzed using the Dunnet test. Results showed that the 24h-LC50 value of Cd applied to Tridacna squamosa veliger was 2.12 mg/L, whereas the NOEC, LOEC, and MATC values were 1 mg/L, 2.5 mg/L, 1.581 mg/L respectively. Mortalities were observed with increasing Cd concentrations. It was also shown a decreasing number of zooxanthellae, damaged in mantle tissue and shells, changes in shell color, released of mantle tissue from the shell with increasing Cd concentrations.